2015
DOI: 10.1097/qai.0000000000000620
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Level Evaluation of the Effect of Antiretroviral Therapy on Cancer Incidence in Kyadondo County, Uganda, 1999–2008

Abstract: Background The introduction of antiretroviral therapy (ART) in the US and Europe has led to changes in the incidence of cancers among HIV- infected persons, including dramatic decreases in Kaposi sarcoma (KS) and non-Hodgkin lymphoma (NHL), and increases in Hodgkin lymphoma (HD), liver and anogenital malignancies. We sought to evaluate whether increasing availability of ART is associated with changing cancer incidence in Uganda. Methods Incident cases of 10 malignancies were identified from Kampala Cancer Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 30 publications
2
33
1
Order By: Relevance
“…Our observed prevalence in 2014 of 5% is consistent with other studies (3–7.1% [30]). While globally the incidence of Kaposi sarcoma is decreasing with increasing ART coverage [31,32], we observed increasing prevalence over time, reaching 3.6% among patients enrolled in 2014 with low CD4 count, most likely due to improved detection, although the limitations of physician-diagnosis are known [33]. Among the same KIULARCO patients, PCP prevalence was lower than in a recent meta-analysis of studies conducted between 1995 and 2015 (5.8% versus 15.4%) but the authors found substantial heterogeneity by time, clinical setting and diagnostic method [34].…”
Section: Discussionmentioning
confidence: 99%
“…Our observed prevalence in 2014 of 5% is consistent with other studies (3–7.1% [30]). While globally the incidence of Kaposi sarcoma is decreasing with increasing ART coverage [31,32], we observed increasing prevalence over time, reaching 3.6% among patients enrolled in 2014 with low CD4 count, most likely due to improved detection, although the limitations of physician-diagnosis are known [33]. Among the same KIULARCO patients, PCP prevalence was lower than in a recent meta-analysis of studies conducted between 1995 and 2015 (5.8% versus 15.4%) but the authors found substantial heterogeneity by time, clinical setting and diagnostic method [34].…”
Section: Discussionmentioning
confidence: 99%
“…Most African countries lack population-based cancer registry data that allow an assessment of cancer burden. Nonetheless, analyses of incidence data from cancer registries in Uganda and Botswana provide evidence for recent declines in KS that are temporally associated with uptake of HAART [47, 48]. …”
Section: Hiv and Cancer In The Developing Worldmentioning
confidence: 99%
“…Similarly, in both China and Brazil, relative ADC declines and NADC increases are occurring as in high-income countries [16*, 17*]. Conversely, in most of SSA, ADC still dominate with incidence declines most consistently observed for KS, although KS incidence remains high throughout the region and is often among the most frequent cancers overall [15**, 18*, 19*, 20, 21**, 22]. HIVAM are therefore unlikely to recede as a public health problem in LMIC in the near term despite ART scale-up.…”
Section: Epidemiologymentioning
confidence: 99%